Beliefs of Students, Parents and Teachers on Use of Unauthorized Study Materials and Success in Secondary Mathematics Education in Nepal - Bhattarai, Laxmi Prasad; Upadhyaya, Hari Prasad (Nepal Journal of Multidisciplinary Research, 2020)
Most of the Nepali students have been widely found using different unauthorized book and study materials for achieving good results in their exams in secondary levels as well as higher levels of education. Theseunauthorized books and study materials have been found usefulas they are mostly exam oriented and have the detailed worked out questions and answers from the past years asked by the examination board of Nepal.A study was conducted to examine the usefulness of such materials in mathematics of secondary level education. It was also aimed to assess the beliefs of students, parents and teachers on the use of unauthorized study materials and achieve success in the secondary mathematics education in Nepal. By using semi-structured questionnaire with students and key informant interviews with selected parents/guardians and mathematics teachers, the researcher has explored the achievements of students and beliefs and attitudes of students along with perspectives of their parents and math teachers.